Influence of taxonomic, functional, and phylogenetic diversity on the biomass production of plankton communities - Carao, Farrah Sharyl C. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Plankton are important food sources for different species in the marine ecosystem and fluctuations in their composition and diversity influence the feeding habits of fishes. However, studies regarding community diversity focused on only one planktonic group and have not considered that the group changes with respect to their environment even though a group changes with its environment. Although the effects of biodiversity on ecosystem functioning are well-studied in terrestrial and freshwater ecosystems, its effects in marine ecosystems are understudied. Here, the influence of biodiversity on the ecosystem function was investigated by relating the taxonomic, functional, and phylogenetic diversities of phytoplankton and zooplankton to their biomass using type I linear regression. Results showed that the variance in the phytoplankton biomass was not significantly explained by zooplankton taxonomic diversity and phytoplankton phylogenetic diversity. However, variance in zooplankton biomass was significantly explained by zooplankton taxonomic diversity and phytoplankton species richness. Also, the biomass of net phytoplankton community had moderate positive relationship with zooplankton richness and phytoplankton phylogenetic diversity, and a moderate negative relationship with zooplankton evenness. Although the proportion of variance in the phytoplankton biomass explained by zooplankton taxonomic diversity, was not significant, it is worth noting that this may point to a top-down control exerted, both richness and evenness, by zooplankton on the phytoplankton community. Additionally, results showed that zooplankton biomass has a significant negative relationship with species evenness. The findings of this study support the hypothesis that greater diversity in the higher trophic level would lead to an increase in their biomass and a top-down control on the organisms at the lower trophic level.